Chemical and microbial characterization of washed rice water waste to assess its potential as plant fertilizer and for increasing soil health - Nabayi, Abba; Teh, Christopher Boon Sung; Tan, Ali Kee Zuan; Tan, Ngai Paing; Mat Akhir, Nurul Izzati (Multidisciplinary Digital Publishing Institute, 2021)
The wastewater from washed rice water (WRW) is often recommended as a source of plant nutrients in most Asian countries, even though most current research on WRW lack scientific rigor, particularly on the effects of rice washing intensity, volumetric water-to-rice ratio (W:R), and condition of the WRW before plant application. This research was thus carried out: (1) to determine how various rice washing intensities, fermentation periods (FP), and W:R would affect the nutrient content in WRW, and (2) to isolate, identify, and characterize the bacterial community from fermented WRW. The WRW was prepared at several rice washing intensities (50, 80, and 100 rpm), FP (0, 3, 6, and 9 days), and W:R (1:1, 3:1, and 6:1). The concentrations of all elements (except P, Mg, and Zn) and available N forms increased with increasing FP and W:R. Beneficial N-fixing and P- and K-solubilizing bacteria were additionally detected in WRW, which helped to increase the concentrations of these elements. Monovalent nutrients NH+4-N, NO−3−N, and K are soluble in water. Thus, they were easily leached out of the rice grains and why their concentrations increased with W:R. The bacteria population in WRW increased until 3 days of fermentation, then declined, possibly because there was an insufficient C content in WRW to be a source of energy for bacteria to support their prolonged growth. While C levels in WRW declined over time, total N levels increased then decreased after 3 days, where the latter was most possibly due to the denitrification and ammonification process, which had led to the increase in NH+4-N and NO−3−N. The optimum FP and W:R for high nutrient concentrations and bacterial population were found to be 3 to 9 days and 3:1 to 6:1, respectively. WRW contained nutrients and beneficial bacterial species to support plant growth.